Analisis Kepuasan Konsumen di Restoran Canting Semarang - Nugraheni, Krisnawati Setyaningrum; Octafian, Ray (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2020)
Consumer satisfaction is influenced by product quality and service satisfaction variables are independent variables, while customer satisfaction is the dependent variable. To find out the magnitude of the effect of product quality, facilities and location on customer satisfaction, in sampling using the Slovin formula obtained at 87 with an error rate of 10%. The sampling technique uses the method of accidental sampling which is done by obtaining data from a group of population, then incidentally or incidentally by not using a particular plan. R2 value of 0.821, meaning that 82.1% of customer satisfaction can be explained by the variable quality of products, facilities and location while 17.9% is explained by other variables.